Education Of Health Cadres with Methods Emotional Demonstration (Emo Demo) Asi Only Enough - Niluh Nita Silfia; Artika Dewie; Asri Widyayanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The Emo Demo strategy is the arrangement of advising with the procedure of conveying messages that are given in a straightforward, fun and contacting feeling, animating the objective of directing to effortlessly recollect the message given. As one of the directing procedures with respect to elite breastfeeding, instruction for wellbeing units is done on the Emo Demo-ASI Only Enough technique which intends to build the information and abilities of wellbeing frameworks in the Dolo Health Center working region in giving advising utilizing the Emo Demo-ASI just Enough strategy. This people group administration is through giving materials and exhibits to sharpen the abilities of wellbeing frameworks who are engaged with advising exercises, particularly about elite breastfeeding as one of the anticipation of hindering in the workspace of the Dolo Health Center. This movement is completed in gatherings, starting and finishing with a pre-test and post-test. The aftereffects of this review show an expansion in information on most of wellbeing units as much as 72.5%. With a restricted time, after an exhibition and practice of the abilities of the Emo demo-ASI technique was adequate, from the past 100% incompetent, it was seen that few wellbeing frameworks had the option to rehearse the emotional demo-ASI strategy, just 10% were talented.